2013
DOI: 10.1136/heartjnl-2013-304163
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids induce arrhythmias in human atrial myocardium—implications for altered serum bile acid composition in patients with atrial fibrillation

Abstract: High TCA concentrations induce arrhythmias in adult human atria while ursodeoxycholic acid does not. AF is associated with higher serum levels of non-ursodeoxycholic bile acid conjugates and low levels of ursodeoxycholic acid conjugates. These data suggest that higher levels of toxic (arrhythmogenic) and low levels of protective bile acids create a milieu with a decreased arrhythmic threshold and thus may facilitate arrhythmic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 35 publications
6
54
0
3
Order By: Relevance
“…Using isolated human atrial trabeculae, the authors demonstrate that TCA has a dose-dependent increase in arrhythmic extra contractions, without affecting key functional parameters of the heart such as contractile force, diastolic tension and relaxation. They further show that hydrophilic bile acid ursodeoxycholic acid (UDCA) and its taurine conjugate do not induce arrhythmias even at high concentrations 12. These human experiments, which were faithfully reproduced in isolated adult mouse cardiomyocytes, further strengthen the long-held notion that high levels of circulating bile acids adversely affect myocardial cell biology.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Using isolated human atrial trabeculae, the authors demonstrate that TCA has a dose-dependent increase in arrhythmic extra contractions, without affecting key functional parameters of the heart such as contractile force, diastolic tension and relaxation. They further show that hydrophilic bile acid ursodeoxycholic acid (UDCA) and its taurine conjugate do not induce arrhythmias even at high concentrations 12. These human experiments, which were faithfully reproduced in isolated adult mouse cardiomyocytes, further strengthen the long-held notion that high levels of circulating bile acids adversely affect myocardial cell biology.…”
mentioning
confidence: 70%
“…It is possible that hydrophobic bile acids such as TCA, by virtue of their ‘detergent’-like properties alter the composition and structure of the cardiomyocyte cell membrane causing a direct damage to the cardiac ion channels, thus affecting Ca 2+ signalling as this12 and other studies imply 26–28. It is also possible that the bile acids exert intracellular effect on pathways that regulate Ca 2+ homoeostasis and signalling through membrane receptors such as muscarinic receptors29 or the newly discovered bile acid receptor TGR5 which is present in rodent, rabbit and human hearts 1 13 30…”
mentioning
confidence: 84%
“…Phospholipid membrane on platelets has been implicated as critical for these cells to aggregate and degranulate [12]. However bile acids also activate a number of cellular calcium related channel receptors [5,13,14]. Calcium regulation is critical for multiple platelet functions [15], and may be another mechanism for TUCA inhibition of platelets.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro TUCA causes angiogenesis and cell proliferation [4]. Elevated blood TUCA levels have also been implicated with heart arrhythmias [5], suggesting that this is a highly active biologic molecule. In rat models, it has been shown that serum taurocholic acid levels markedly rise following acute liver injury [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…As UDCA is currently in use for clinical treatment of both ICP and other cardiac diseases (Geenes and Williamson, 2009;Geenes et al, 2014Geenes et al, , 2013Rainer et al, 2013;Von Haehling et al, 2012), the short term and long term effects of UDCA on neonatal cardiomyocytes and fibroblasts were investigated. Optical recording of calcium transients was carried out with control (HBSS) solution, followed by UDCA treatment (10 nM, 100 nM, 1 μM or 100 μM).…”
Section: The Effect Of Udca On the Heartmentioning
confidence: 99%